Fatwas, Religious Moderation, and Global Security: Examining the Intersection of Islamic Economic Jihad and Humanitarian Responses to the Israel-Palestine Conflict - Zunaidi, Arif; Maghfiroh, Fachrial Lailatul; Azmi, Nurul Athirah Mohd (IAIN Ponorogo, 2025)
This research examines the implications of the Indonesian Ulema Council's (MUI) Fatwa No. 83 of 2023, which supports the Palestinian struggle against Israeli occupation, focusing on its theological foundations, the concept of religious moderation, and the dynamics of economic jihad through the boycott of Israeli products. Utilizing a qualitative approach, this study analyzes the fatwa's position within Islamic jurisprudence and its impact on global humanitarian responses to the Israel-Palestine conflict. The findings indicate that the fatwa serves as a non-violent instrument, promoting peace and human rights while advocating for humanitarian aid to Palestine through zakat, Infāq, and donations. It also highlights the potential effects on Indonesia's foreign policy, urging the government to take a firmer stance in international relations regarding Palestine. Furthermore, the study discusses the effectiveness of the boycott as an economic strategy and its moral implications, emphasizing the importance of addressing the humanitarian concerns of civilians in both Israel and Palestine. Overall, the fatwa reflects a balanced approach to supporting the Palestinian cause while adhering to the principles of moderation and compassion inherent in Islam.